Modern Approaches to the Management of Patients with Hyperkaliemia - E. V. Reznik; A. I. Selivanov; A. R. Lutsenko; L. A. Garanina; G. N. Golukhov (Архивъ внутренней медицины)
Hyperkalemia is the most common electrolyte imbalance in clinical practice. Hyperkalemia can be caused by an increased intake of potassium into the body, the shift of potassium out of cells or an abnormal renal potassium excretion. This condition is associated with a high risk of death from arrhythmias; therefore, even a slight deviation of the serum potassium level from the norm requires immediate correction. Modern approaches to the treatment of hyperkalemia include the elimination of predictors and the potassium-lowering drugs. Although inhibitors of the renin-angiotensin-aldosterone system are currently the best cardionephroprotective drugs, their administration can lead to hyperkalemia too, especially in heart failure, chronic kidney disease and diabetes mellitus. The article discusses in detail the physiology of potassium metabolism, possible predictors, prevention and treatment of hyperkalemia.